Systematic review of efficacy, safety and pharmacokinetics of intravenous and intraventricular vancomycin for central nervous system infections - Liu, Shu-Ping; Xiao, Jing; Liu, Ya-Li; Wu, Yue-E; Qi, Hui; Wang, Zhuang-Zhuang; Shen, A-Dong; Liu, Gang; Zhao, Wei (Frontiers in Pharmacology, 2022)
Objective: The decision of vancomycin dosage for central nervous system (CNS) infections is still a challenge because its bactericidal nature in cerebrospinal fluid (CSF) has not been confirmed by human studies. This study systematically reviewed the literatures on vancomycin in patients with meningitis, ventriculitis, and CNS device-associated infections, to assess efficacy, safety, and pharmacokinetics to better serve as a practical reference. Methods: Medline, Embase, and Cochrane Library were searched using terms vancomycin, Glycopeptides, meningitis, and central nervous system infections. Data were extracted including characteristics of participants, causative organism(s), administration, dosage, etc. The clinical response, microbiological response, adverse events and pharmacokinetic parameters were analyzed. Results: Nineteen articles were included. Indications for vancomycin included meningitis, ventriculitis, and intracranial device infections. No serious adverse effects of intravenous (IV) and intraventricular (IVT) vancomycin have been reported. Dosages of IV and IVT vancomycin ranged from 1000 - 3000 mg/day and 2 - 20 mg/day. Duration of IV and IVT vancomycin therapy most commonly ranged from 3 - 27 days and 2 - 21 days. Therapeutic drug monitoring was conducted in 14 studies. Vancomycin levels in CSF in patients using IV and IVT vancomycin were varied widely from 0.06 to 22.3 mg/L and 2.5 to 292.9 mg/L. No clear relationships were found between vancomycin CSF levels and efficacy or toxicity. Conclusions: Using vancomycin to treat CNS infections appears effective and safe based on current evidence. However, the optimal regimens are still unclear. Higher quality clinical trials are required to explore the vancomycin disposition within CNS.